2021
DOI: 10.3390/en14206449
|View full text |Cite
|
Sign up to set email alerts
|

Research on Heat Exchange Law and Structural Design Optimization of Deep Buried Pipe Energy Piles

Abstract: A deeply buried pipe energy pile (DBP-EP) combines the advantages of a ground source heat pump (GSHP) and an inside buried pipe energy pile (IBP-EP) and is an efficient, clean, and energy-saving technology. Based on field tests and numerical simulations, this paper explores the temperature distribution and heat exchange effects of DBP-EP under different influencing factors. The results show that when the pile-to-well ratio is approximately 0.3–0.4, the heat exchange of the energy pile obtains the best benefit;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…(3) The thermal property of the reinforcement in the pile foundation is the same as that of concrete; (4) Rock and soil temperature around the pile foundation are uniform; (5) The effects of the pipe wall on heat transfer are ignored; (6) The pile-soil contact surface is regarded as rigid unit contact; (7) It is assumed that soil is an ideal elastoplastic model.…”
Section: Basic Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The thermal property of the reinforcement in the pile foundation is the same as that of concrete; (4) Rock and soil temperature around the pile foundation are uniform; (5) The effects of the pipe wall on heat transfer are ignored; (6) The pile-soil contact surface is regarded as rigid unit contact; (7) It is assumed that soil is an ideal elastoplastic model.…”
Section: Basic Assumptionsmentioning
confidence: 99%
“…At the same time, the DBP-EP enables the heat-exchange pipe to pass through the pile end to achieve an ideal depth for heat transfer. Furthermore, the deep buried pipe energy pile (DBP-EP) has a more flexible structure that the design of the pile body, and the relevant size of the deep well can be achieved according to the heat-transfer demand in practical applications, which is a further optimization of the inside buried pipe energy pile (IBP-EP) and the GSHP in the pile [5,6]. Furthermore, this realizes the efficient and economic utilization of geothermal resources as an efficient and feasible idea for the development of low-carbon buildings.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the existence of water in soil has a great role in promoting the efficiency of energy piles [9,[12][13][14]. It is also concluded that the pile diameter ratio, pile spacing, the diameter of the heat exchange tube in the pile, the water flow velocity in the pipe, the inlet water temperature, and the properties of the strata around the energy pile will affect the working efficiency of the energy pile [15][16][17][18][19][20]. In terms of the long-term working performance of the energy pile, the thermal cycle of the energy pile will lead to a decrease in the soil moisture content around the pile, resulting in a decrease in the thermal conductivity of the soil around the pile, which will increase the temperature around the energy pile and reduce the heat exchange efficiency of the energy pile [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of energy piles provides a new opinion for the extensive application of ground source heat pump, which has been widely used because of overcoming the shortcomings of traditional ground source heat pumps. At present, domestic and foreign scholars have carried out a large number of studies on energy piles, covering various aspects such as heat transfer mechanisms, heat exchange enhancement, thermal structural response, and group piles effects [1][2][3][4][5][6][7]. As one of the core components of the energy pile, the circulating working liquid carries heat and circulates in the heat exchanger under the working condition in summer, to release heat into the soil, and absorbs heat from the soil as it flows under the winter condition.…”
Section: Introductionmentioning
confidence: 99%